2018
DOI: 10.1039/c8ce00798e
|View full text |Cite
|
Sign up to set email alerts
|

The thermo-responsive behavior in molecular crystals of naphthalene diimides and their 3D printed thermochromic composites

Abstract: Alteration of the number of carbon atoms on the alkoxyphenyl substituent in naphthalene diimides results in tunable thermo-salient behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…After our discoveries that butoxyphenyl-NDI crystals 9 under temperature gradients exhibit irreversible thermosalience and reversible thermochromism, we expanded our search to other NDI derivatives based on alkyl chain length. 12 We hypothesize that longer chains and smaller ring overlaps might flatten the potential energy curve, thus facilitating the transition and improving the reversibility. Accordingly, we observe that this NDI family exhibits thermosalience and/or thermochromism across its many derivatives.…”
Section: Resultsmentioning
confidence: 96%
“…After our discoveries that butoxyphenyl-NDI crystals 9 under temperature gradients exhibit irreversible thermosalience and reversible thermochromism, we expanded our search to other NDI derivatives based on alkyl chain length. 12 We hypothesize that longer chains and smaller ring overlaps might flatten the potential energy curve, thus facilitating the transition and improving the reversibility. Accordingly, we observe that this NDI family exhibits thermosalience and/or thermochromism across its many derivatives.…”
Section: Resultsmentioning
confidence: 96%
“…After our discoveries that butoxyphenyl-NDI crystals9 under temperature gradients exhibit irreversible thermosalience and reversible thermochromism, we expanded our search to other NDI derivatives based on alkyl chain length. 12 We hypothesize that longer chains and smaller ring overlaps might flatten the potential energy curve, thus facilitating the transition and improving the reversibility. Accordingly, we observe that this NDI family exhibits thermosalience and/or thermochromism across its many derivatives.…”
Section: Resultsmentioning
confidence: 96%
“…9 We have reported that the single-action thermosalient behavior is tunable across temperature ranges by altering the alkyl chain from four to nine carbons. 12 Here we report that, when the alkyl chain is 10 linear carbons, the thermosalient crystals show instantaneous reversible negative thermal expansion. Specifically, the crystals shrink to 90% of its original length instantaneously upon heating beyond 45 °C and, expand back to its original length upon cooling below 35 °C.…”
Section: Introductionmentioning
confidence: 85%